Revitalisierung von brachgefallenen Hafen- und Uferzonen: Transformationsprozesse an der Waterfront - Schubert, Dirk (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
In many ports, dockland areas close to the city centre have become available for urban redevelopment. This article discusses the transformation processes taking place in dockland and riverside zones within the context of the current discourse on urban-development policy; it also describes the renaissance and the transformation in the image of such zones. The author outlines the experience of the changes of use which these areas have undergone, the reasons that led to such sites becoming derelict, and the regeneration process; he also summarises the current state of academic analysis of the subject. Proceeding from a broad-based explanatory approach, the article sets out five phases of the transformation process affecting the relations between city and dockland, concluding with a brief restatement of the importance, the opportunities, problems and risks posed by the redevelopment of dockland and riverside areas.